The right to education in a pluralistic world: balancing the pluralistic approach of the right to education and minimum requirements - Ignasi Grau Callizo (Frontiers in Education)
The core of the right to education lies in its ability to foster the full development of the human personality, as recognized by international human rights treaties. Education is not merely a political or economic tool, but a fundamental human right that enables human beings to engage with the shared cultural, moral, and social achievements of society. In a pluralistic world, where cultural identities are diverse, the right to education must balance the cultural identity with the need for common knowledge and understanding. This balance cannot be achieved without a partnership of trust between families and public authorities through the establishment of human rights based minimum educational standards.